Effect of Exercise on Health and Performance by Long-Haul, High-Stress Steers During the Receiving Period - John R. Jaeger; Justin W. Waggoner; Keith R. Harmoney; Quentin Rupp (Kansas Agricultural Experiment Station Research Reports, 2020)
Morbidity and mortality associated with the bovine respiratory disease (BRD) complex continue to be a significant challenge to the United States beef industry. Stress associated with maternal separation, environment change, transportation, diet changes, and commingling are common to beef industry marketing channels and have been linked to depressed growth and health of recently weaned calves. Cattle originating from the Southeastern U.S. tend to exhibit high rates of BRD after transportation to Great Plains feedlots. Previous research has utilized exercise one time per day or three times per week for the receiving period. In those studies, health performance of cattle was not different from non-exercised cattle and differences in gain performance were minimal. The objective of this research was to examine the effect of exercise four times daily for the first 14 days after arrival on incidence of BRD and animal growth and performance.
Keywords: high-stress steers; bovine respiratory disease; exercise; morbidity; mortality